Situación actual de la sarna e infecciones parasitarias en vicuñas (Vicugna vicugna) de la Región Cusco, Perú - Angulo-Tisoc, José M (2021)
The aim of this study was to identify and evaluate the cases of scabies caused by Sarcoptes scabiei and endoparasites in wild and captive vicuñas (Vicugna vicugna) from the Cusco Region, Peru. Scrapings of skin lesions were made and faecal samples were taken during the capture of vicuñas during the chaccus. The frequency of S. scabiei was 1.9% (54/2826), being 6.1% (48/777) in the wild and 0.2% (6/2049) in captivity. Likewise, F. hepatica (2.0%), Strongylus type eggs (42.1%), Nematodirus sp (6.8%), N. spathiger (26.5%), Trichuris sp (4.0%), Eimeria spp (85.0%), and Moniezia spp (2.7%) were found in a sample of 147 animals, being most cases monoparasitism.sarna